2021
DOI: 10.1101/2021.07.21.453115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and Temporal Organization of Composite Receptive Fields in the Songbird Auditory Forebrain

Abstract: The mechanisms underlying how single auditory neurons and neuron populations encode natural and acoustically complex vocal signals, such as human speech or bird songs, are not well understood. Classical models focus on individual neurons, whose spike rates vary systematically as a function of change in a small number of simple acoustic dimensions. However, neurons in the caudal medial nidopallium (NCM), an auditory forebrain region in songbirds that is analogous to the secondary auditory cortex in mammals, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In a recent study, we have demonstrated that CRFs of neurons are independent of the neurons' distance, location and, topology [28]. The stimuluslocked properties of recorded cells by the Epi-Intra probe proved to be useful in making them viable candidates for CRFs extraction.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a recent study, we have demonstrated that CRFs of neurons are independent of the neurons' distance, location and, topology [28]. The stimuluslocked properties of recorded cells by the Epi-Intra probe proved to be useful in making them viable candidates for CRFs extraction.…”
Section: Discussionmentioning
confidence: 97%
“…As starters, to extract high quality composite receptive fields from neuron cell responses, the cell responses should be stimulus-locked with low noise [27,28]. Since the recorded cells by Epi-Intra probe exhibit such properties, as shown earlier, we were then able to extract CRFs from them quite easily.…”
Section: Statistical Analysis Of Electrophysiological Recordingsmentioning
confidence: 94%
See 2 more Smart Citations
“…To relate stimulus representations to neural activity, we computed composite receptive fields (CRFs) for auditory cortical neurons using the Maximum Noise Entropy (MNE) method (Fitzgerald et al, 2011). Previous work has shown that the MNE model well-describes the sensitivity to higher-order features exhibited by NCM neurons (Kozlov & Gentner, 2016;Vahidi, 2021).…”
Section: Auditory Single Neurons Respond To Multiple Distinct Feature...mentioning
confidence: 99%